Effects of working parameters on the performance of cyclone separator for rapeseed combine harvester based on CFD - Wan, Xingyu; Yuan, Jiacheng; Yang, Jia; Liao, Yitao; Liao, Qingxi (International Journal of Agricultural and Biological Engineering, 2023)
Existing development for cyclone separation cleaning components of the rapeseed combine harvester, which employs the suspending airflow to separate the rapeseeds from the materials other than grain (MOG), has the challenge to figure out the optimal working parameters, highlighting a need for exploration of the invisible airflow based on Computational Fluid Dynamics (CFD). The airflow status was mainly affected by the air velocities of the inlet, and the outlet for the MOG. The single factor and response surface experiments were carried out. It could be found that the inlet and MOG outlet velocities affected the air velocities through the change in the air quantity. Furthermore, the mathematical model of the relationship between the air velocities inside the cyclone and the working parameters was built, and the optimal combination of working parameters was obtained by multi-objective optimization. The inlet and outlet velocities of the optimal combination were 4.25 m/s and 29.87 m/s, respectively. Under this condition, the cleaning ratio and loss ratio of the cleaning device was 94.62% and 5.39%, respectively, as validated by the field experiment. The findings provide references for the improvement of cleaning systems for rapeseed combine harvesters. Keywords: rapeseed, combine harvester, cyclone separation cleaning, optimal working parameters, CFD DOI: 10.25165/j.ijabe.20231601.7253 Citation: Wan X Y, Yuan J C, Yang J, Liao Y T, Liao Q X. Effects of working parameters on the performance of cyclone separator for rapeseed combine harvester based on CFD. Int J Agric & Biol Eng, 2023; 16(1): 128–135.